Desain furnitur hasil kajian seting fisik kelas studio berbasis perilaku mahasiswa milenial - Dwi Sulistyawati; Imam Santosa; Deddy Wahyudi (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2020)
Activities and behavior Millennials have special characteristics, as a result of being influenced by information technology tools that bring about changes in various aspects that can have an impact on the problem. The starting point of the problem that must be solved is that the behavior of Millennial students behaves in terms of the learning process in accordance with the applicable curriculum to get the right means of space (physical arrangement) so that it is expected to contribute to the effectiveness in achieving the target of the learning process, which refers to research on activities users, especially the activities of millennial generation lecturers and students in behaving in class. Physical Setings Products that can show the relationship between spatial conditions, needs and behavior of millennial students in class. The results of this study then become the basis for creating a classroom arrangement model that is tailored to the curriculum and characteristics of millennial students.